TGFβ1 Controls PPARγ Expression, Transcriptional Potential, and Activity, in Part, through Smad3 Signaling in Murine Lung Fibroblasts. (10th September 2012) - Ramirez, Allan; Ballard, Erin N.; Roman, Jesse
Abstract : Transforming growth factor β 1 (TGF β 1) promotes fibrosis by, among other mechanisms, activating quiescent fibroblasts into myofibroblasts and increasing the expression of extracellular matrices. Recent work suggests that peroxisome proliferator-activated receptor γ (PPAR γ ) is a negative regulator of TGF β 1-induced fibrotic events. We, however, hypothesized that antifibrotic pathways mediated by PPAR γ are influenced by TGF β 1, causing an imbalance towards fibrogenesis. Consistent with this, primary murine primary lung fibroblasts responded to TGF β 1 with a sustained downregulation of PPAR γ transcripts. This effect was dampened in lung fibroblasts deficient in Smad3, a transcription factor that mediates many of the effects of TGF β 1. Paradoxically, TGF β 1 stimulated the activation of the PPAR γ gene promoter and induced the phosphorylation of PPAR γ in primary lung fibroblasts. The ability of TGF β 1 to modulate the transcriptional activity of PPAR γ was then tested in NIH/3T3 fibroblasts containing a PPAR γ -responsive luciferase reporter. In these cells, stimulation of TGF β 1 signals with a constitutively active TGF β 1 receptor transgene blunted PPAR γ -dependent reporter expression induced by troglitazone, a PPAR γ activator. Overexpression of PPAR γ prevented TGF β 1 repression of troglitazone-induced PPAR γ -dependent gene transcription, whereas coexpression of PPAR γ and Smad3 transgenes recapitulated the TGF β 1 effects. We conclude that modulation of PPAR γ is controlled by TGF β 1, in part through Smad3 signals, involving regulation of PPAR γ expression and transcriptional potential.